Assessment of academic achievement among minority migrant children in China - Zelin, Su; Azam, Naqi Dahamat; Arshat, Zarinah; Rosnon, Mohd Roslan (Human Resource Management Academic Research Society, 2023)
Low academic achievement stands as a major challenge for migrant children from ethnic minorities in China. This social problem can cause other problems, such as dropping out and poor future outcomes. However, current approach in evaluating academic performance among migrant children from ethnic minorities is solely based on the student's grades. This evaluation system seems do not meet the requirements of China's compulsory education quality indicators. Therefore, this study proposed a new approach in measuring academic achievement in minority migrant children by considering four dimensions, namely academic, moral, physical-mental, as well as overall personal development (including two parts of aesthetic quality and labor and practice). A total of 538 minority migrant adolescents in China aged 13 to 15 years old participated. We conducted item and factor analyses on sample 1 (n= 147) and a version with 17-item measurement was formed. We ran correlation, reliability test, and factor analysis on sample 2 (n = 391) to access the reliability and validity of the measure. The results showed a good reliability and validity to assess the academic achievement in migrant children of ethnic minorities in China